2012
DOI: 10.1093/brain/aws299
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin derivatives promote Schwann cell differentiation and improve neuropathy in R98C CMT1B mice

Abstract: Charcot-Marie-Tooth disease type 1B is caused by mutations in myelin protein zero. R98C mice, an authentic model of early onset Charcot-Marie-Tooth disease type 1B, develop neuropathy in part because the misfolded mutant myelin protein zero is retained in the endoplasmic reticulum where it activates the unfolded protein response. Because oral curcumin, a component of the spice turmeric, has been shown to relieve endoplasmic reticulum stress and decrease the activation of the unfolded protein response, we treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 46 publications
(87 reference statements)
4
98
0
Order By: Relevance
“…This permitted us to correlate UPR activation in our assays with the clinical presentations of the patients. Previous studies have shown that Ser63del and Arg98Cys MPZ cause UPR activation and that tuning of the UPR results in improvement of cellular and rodent disease models in mice with these mutations 4, 5, 8, 9, 10. Therefore, we believed it appropriate to consider any values higher than those observed from Ser63del and Arg98Cys MPZ as significantly activating the UPR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This permitted us to correlate UPR activation in our assays with the clinical presentations of the patients. Previous studies have shown that Ser63del and Arg98Cys MPZ cause UPR activation and that tuning of the UPR results in improvement of cellular and rodent disease models in mice with these mutations 4, 5, 8, 9, 10. Therefore, we believed it appropriate to consider any values higher than those observed from Ser63del and Arg98Cys MPZ as significantly activating the UPR.…”
Section: Discussionmentioning
confidence: 99%
“…48 h after transfection, immunocytochemistry was carried out 9. In brief, cells were rinsed twice in PBS for 5 min, fixed in 4% paraformaldehyde for 5 min and washed again three times in 1xPBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three arms of the UPR work together in part to relieve ER stress by reducing the overall translation of proteins by the cell 35. Therapies directed at relieving ER stress and attenuating the UPR have improved the neuropathy of both Ser63del33, 36 and Arg98Cys16 mice. Our data suggest that this process may also occur with PMP22Δ4 , further expanding the role of ER stress and UPR activation in the pathogenesis of what are often more severe forms of CMT1.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were transfected with the following plasmids: (1) WT‐PMP22, (2) PMP22‐exon 4 deletion – each plasmid with the hemagglutinin epitope tag fused to the N‐terminus. Forty‐eight hours after transfection, immunocytochemistry was carried out as described previously16). In brief, cells were rinsed twice in PBS for 5 min and then fixed in 4% paraformaldehyde for 5 min.…”
Section: Methodsmentioning
confidence: 99%